Implementation of Lean Manufacturing and Waste Minimization to Overcome Delay in Metering Regulating System Fabrication Process using Value Stream Mapping and VALSAT Method Approach (Case Study: Company YS) - Adizty Suparno; Muhammad Kholil; Farichatus Sa’diyah; Sulaiman Bin H Hasan (Institute for Research on Innovation and Industrial System (IRIS), 2021)
Company YS participates in managing the natural gas network by creating a Metering Regulating System (MRS), which is a tool to measure gas usage and damage to the natural gas network. Based on the data obtained, the MRS delivery process was often not in accordance with the agreed schedule, there was a delay of up to 46%, namely 50 days late from the planned schedule. To overcome these delays, waste reduction is carried out by mapping the overall condition of the company in Value Stream Mapping (VSM) and mapping in detail with the Value Stream Mapping Analysis Tools (VALSAT). In the VSM method, a Current Value Stream Mapping is carried out which then identifies the waste in which the correlation score between the wastes is described in a matrix called the Waste Relationship Matrix then followed by the calculation of the Waste Assessment Questionnaire. Then in the VALSAT method, further waste identification was carried out using seven tools. The most influential percentage of waste that has been obtained is then searched for the root cause using a fishbone diagram and then eliminated and depicted in the Future Value Stream Mapping. The most influential waste in the fabrication process is Waiting and after repairs according to the recommendations, the lead time is obtained from 41,822.60 minutes or 99 working days to 35,055.60 minutes or 83 working days so that the fabrication process can be completed 3 days faster than scheduled.